Differential Association Between Default Mode Network Connectivity and Attachment Styles in Healthy Individuals and Crohn's Disease Patients - Alessandro Agostini; Sara Ventura; Silvia Tempia Valenta; Fernando Rizzello; Paolo Gionchetti; Francesca Benuzzi; Nicola Filippini (Brain and Behavior, 2025)
ABSTRACT Aim Crohn's disease (CD) is associated with psychological disorders and insecure attachment styles, potentially reflecting the long‐lasting disease effect. Although functional magnetic resonance imaging (fMRI) studies revealed differences in CD patients relative to HC, the brain properties underlying the attachment dimensions in CD remain scarcely investigated. We carried out an fMRI study to investigate the neural substrate of the attachment dimensions in CD patients and healthy controls (HCs). Materials and Method Nineteen CD patients and 18 HC were included in this study. All participants filled out the Attachment Style Questionnaire (ASQ) widely used to evaluate the dimensions of the attachment style and underwent an MRI protocol including structural and functional scans. Results The ASQ scores were similar between groups. Concerning the resting fMRI data, we identified two opposite trajectories for the association between two ASQ subscales reflecting attachment insecurity and the default mode network (DMN) connectivity between the two study groups. For the HC, higher scores at the ASQ were associated with reduced DMN connectivity, whereas in CD patients were related to increased DMN connectivity. The significant clusters were located in the superior frontal gyrus, posterior cingulate, and orbito‐frontal regions. Conclusion DMN is involved in higher mental functions including self‐consciousness and affective processes. In CD patients, the DMN modifications associated with attachment insecurity might reflect dysfunctional monitoring of the self and the significant relationships potentially involved in the development of psychological stress and decreased mentalization. Our study strengthens the notion that the attachment dimensions should be considered in the treatment of IBD and encourages novel psychotherapeutic approaches based on mentalization.